Formulation parameters and release mechanism of theophylline loaded ethyl cellulose microspheres - Capomacchia, Anthony C. (2011)
Altering the combined hydrophilic-lipophilic balance (CHLB), by varying the ratio of dual surfactants, on formulation parameters and in vitro drug release of ethyl cellulose microspheres was examined. Theophylline, a xanthine bronchodilator was used to model controlled release owing to its narrow therapeutic index. Microspheres were prepared using different ratios of dual surfactant in an emulsion-solvent evaporation process. Drug loading, encapsulation efficiency, particle size distribution, and geometric mean diameters were evaluated. Drug release was evaluated using several kinetic models including zero and first order, Higuchi square root, and Hixson-Crowell. Microspheres presented as mostly spherical particles and diffusional drug release was affected by microsphere construction. For this novel, dual surfactant system the microsphere matrix is a hydrophobic polymer and the release rate may be modulated with variation in ratio of dual surfactants. Dissolution data followed the Higuchi model and supports the formation of a monolithic microsphere matrix that releases theophylline by Fickian diffusion. Dual surfactants for preparation of microspheres are an inadequately studied research area that offers another means to modulate particle size and drug release. For the current study microspheres prepared with surfactant ratios of Span 65: Tween 40 between 3:1 and 2:1 provided the best control of size and drug release.